(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The importance of health to buyers has increased, and more individuals are becoming conscious of the benefits of consuming nutritious drinks like herbal tea. Moreover, healthy green tea protects against several fatal diseases. The production of green tea is expanding worldwide, especially in India. The sector has grown significantly due to significant customer interest and expenditure. The market for green tea in India was worth US 1,247.36 million in 2018 and is anticipated to rise to US 2,112.47 million by 2027 at a compound annual growth rate (CAGR) of 6.1%. Lipton green tea is among India’s most widely used green tea products.